Performance of an Anaerobic Baffled Reactor (ABR) in treatment of cassava wastewater - Ferraz,Fernanda M. (2009)
The performance of an anaerobic baffled reactor (ABR) was evaluated in the treatment of cassava wastewater, a pollutant residue. An ABR divided in four equal volume compartments (total volume 4L) and operated at 35°C was used in cassava wastewater treatment. Feed tank chemical oxygen demand (COD) was varied from 2000 to 7000 mg L-1 and it was evaluated the most appropriated hydraulic retention time (HRT) for the best performance on COD removal. The ABR was evaluated by analysis of COD (colorimetric method), pH, turbidity, total and volatile solids, alkalinity and acidity. Principal component analysis (PCA) was carried to better understand data obtained. The system showed buffering ability as acidity decreased along compartments while alkalinity and pH values were increased. There was particulate material retention and COD removal varied from 83 to 92% for HRT of 3.5 days.